Refrigerating system of rack - YAN YANGTE; ZHONG WENHUI (2017)
The utility model discloses a refrigerating system of rack, including absorber and generator, the absorber is through first pipe connection generator, and be equipped with generator pump and heat exchanger on the first pipeline, first pipeline is followed the bottom of absorber is connected to the bottom of generator, the condenser is connected to the generator, the condenser passes through the pipe connection evaporimeter, the evaporimeter passes through the evaporimeter pump and connects the shower, air exhaust device is connected to the evaporimeter. The utility model relates to a novelty, simple structure realizes double -cylinder's circulation refrigerating system, and low temperature cold water is prepared to furthest's the heat that utilizes heat source water, and energy -concerving and environment -protective, circulation reuse has saved a large amount of energy. 本实用新型公开了机柜的制冷系统，包括吸收器和发生器，所述吸收器通过第管道连接发生器，并且所述第管道上设有发生器泵和换热器，所述第管道从所述吸收器的底部连接到所述发生器的底部，所述发生器连接冷凝器，所述冷凝器通过管道连接蒸发器，所述蒸发器通过蒸发器泵连接喷淋管，所述蒸发器连接抽气装